The extent of Utilization of the Library Services of Bestlink College of the Philippines: Towards a Library Personnel’s Guidebook (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Building a library usually costs millions including the collections, facilities, and the provision of the different library services intended for the clients. In this context, the researchers would like to assess the Extent of Utilization of the Library Services of Bestlink College of the Philippines: towards a library personnel’s guidebook. The researchers made use of a descriptive method. The respondent of the study covered the four hundred (400) students, irrespective of their courses, to answer the self-made questionnaires, unstructured interviews, and focused group discussions. The result of the study showed that the most familiar and used services offered by the library were Baggage Counter Services. These services were learned from their professors/teachers. The extent of awareness towards the services provided by the personnel of the library is moderate. There were also problems encountered by the clients in terms of policy; the respondents were not favorable with the policy of “No Library Card, No Entry". In terms of collection, most of the books in the library were outdated and library personnel was not approachable to their clients. Finally, in terms of services, sometimes the services in the library were not available for the reason that no library staff operates the services. All these findings may be utilized in crafting a guide to improve the utilization of the library services of Bestlink College of the Philippines. The researchers concluded that library services were not well maximized. Hence, as their recommendation, they crafted a guidebook for the library personnel that will serve as their guide to enhance and improve the utilization of library services at Bestlink College of the Philippines.
Keywords: library science, BCP